A 1.2 V, 3.0 ppm/°C, 3.6 μA CMOS bandgap reference with novel 3-order curvature compensation. (February 2018) - Liu, Lianxi; Huang, Wenbin; Mu, Junchao; Zhu, Zhangming; Yang, Yintang
Abstract: This paper presents a bandgap reference with a high-order curvature compensation circuit which can improve the temperature coefficient (TC) in a wide temperature range. The proposed compensation circuit includes a second-order and a third-order curvature current generators as well as an I-V converter. These two curvature currents are achieved by utilizing the exponential behavior of sub-threshold MOSFET and used for compensating the high-order temperature dependence of BJT base-emitter voltage via I-V converter. The proposed BGR is implemented in a CMOS 0.18 μm process with the active area of 0.056 mm 2 . Measurements on ten samples showed that at the minimum supply voltage 1.2 V, the TC varies from 1.7 to 6.9 ppm/°C over a temperature range of 170 °C (−45 °C–125 °C) with an average value of 3.0 ppm/°C and the total current consumption of 3.6 μA at room temperature. In the supply voltage range of 1.2–1.8 V, the line regulation (LR) is 0.025%/V.